2017
DOI: 10.18227/1982-8470ragro.v10i4.3342
|View full text |Cite
|
Sign up to set email alerts
|

Partição de nutrientes na parte aérea do meloeiro ‘Goldex’ fertirrigado

Abstract: Resumo: O meloeiro é uma das culturas que mais exportam nutrientes com a colheita dos frutos, sendo, ainda, uma das que menos restituem nutrientes ao solo, especialmente quando os restos culturais são retirados da área. Assim, objetivou-se determinar a extração de macro e de micronutrientes pelo fruto, assim como sua proporção em relação a parte aérea durante o desenvolvimento do melão amarelo. O experimento foi instalado segundo o delineamento em blocos casualizados, com quatro repetições. Os tratamentos corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 8 publications
1
2
0
1
Order By: Relevance
“…Subsequently, there was a reduction of this element in vegetative phytomass, and it was redirected to fruit formation. Results similar to that of the present study were reported by Araujo, Oliveira, and Oliveira (2016), who studied the partition of nutrients in 'Goldex' melon and obtained average N contents of 25.48 and 20.95 g kg -1 at 49 DAT and 63 DAT, respectively. At 62 DAT (Figure 2A), K showed a maximum value of 49.91g kg -1 with N and K fertilization of 50 and 15 kg ha -1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…Subsequently, there was a reduction of this element in vegetative phytomass, and it was redirected to fruit formation. Results similar to that of the present study were reported by Araujo, Oliveira, and Oliveira (2016), who studied the partition of nutrients in 'Goldex' melon and obtained average N contents of 25.48 and 20.95 g kg -1 at 49 DAT and 63 DAT, respectively. At 62 DAT (Figure 2A), K showed a maximum value of 49.91g kg -1 with N and K fertilization of 50 and 15 kg ha -1 , respectively.…”
Section: Resultssupporting
confidence: 92%
“…Mg is behaviorally similar to Ca. Although it is redistributed to a greater extent in the plant, Mg + has the xylematic pathway as the predominant pathway, and its availability in the soil influences its distribution to the reproductive organs of the plant (Araújo et al, 2017). However, the dynamics of accumulation in each part of the plant were similar to those found by Mendoza-Cortez et al ( 2014), with the leaves having the highest amounts observed, followed by the fruits and the stem with the lowest values.…”
Section: Resultssupporting
confidence: 75%
“…The increase in each plant organ occurred in a quadratic manner, where the leaf alone accumulated approximately 75% of the total (903.88 g or 1.99 lb ha -1 ) at the 64 th DAE. This greater demand can be attributed to the role of Fe in the synthesis of chlorophyll and consequently in photosynthesis (Araújo et., 2017). However, the fruits only accumulated 264.33 g (0.58 lb) ha -1 at the 64 th DAE, which was 20% of the total Fe, in contrast to the findings of Melo et al (2013), where the fruits at 70 days after transplanting obtained a value of 8.48 mg plant -1 (141.33 g or 0.31 lb ha -1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Em relação ao micronutriente Fe, Araújo et al (2016) trabalhando com frutos de meloeiro relataram comportamento similar ao verificado no presente estudo. Esses mesmo autores observaram que o fruto é o dreno preferencial deste micronutriente.…”
Section: ----------------------G Kg -1 ------------------------------unclassified